(untitled) (Journal of Nepal Geological Society, 2016)
Detailed geological mapping was carried out in Dandli of the Kotli district where Middle Cambrian to Late Miocene rocks are exposed. The coal bearing Patala Formation of the Upper Paleocene epoch is well exposed on both limbs of the doubly plunging Tattapani-Karela anticline and also on the eastern plunge of the doubly plunging Devigarh-Palana anticline. These anticlines are considered as the continuation of the Riasi anticline in Jammu, India. Structurally, the Kotli area lies to the south east of the Hazara-Kashmir Syntaxis. The 73.2 m thick Patala Formation contains two coal seams. The exposed thickness of individual seam ranges from 1 m to 1.2 m and in the underground, it reaches upto 4 m at some places. The coal from the Dandli area has medium volatiles and low moisture with generally low ash content and good fixed carbon. Sulphur content varies from 0.51 to 3.17% and occurs in the form of pyrite nodules. The chemical analyses reveal that the coal is bituminous to semi-anthracite variety.